Some Protozoan Species Inhabiting the East Bank Sediment of River Tigris in Baghdad City - Kadhim, Zahraa; Mahmood, Suhaila (Iraqi Journal of Science, 2023)
There are no researches in Iraq concerned identification and ecology of protozoa in sediment. The present study has been dealt with free-living protozoa community of the Tigris river bank sediment in Baghdad city. Variable species of vegetation (reeds and wild grasses) were observed to grow at both sides of the river.For the present study three sites were chosen at the east side of river Tigris. Monthly samples were collected from the sediment of each site over a period from January to October 2012.Total of 22 taxa were found, 12 of ciliates, 5 of each flagellates and sarcodines in the sediment samples. The highest numbers of protozoan 15 taxa were recorded from each of the sites 1&3 and little less taxa (13) were found in site 2. Among ciliates community Cyclidium sp. and Uronema marinum were found constantly in all investigated sites, meanwhile Cinetochilum sp. and Stylonychia sp. were belonged to accessory taxa. Among the testacies community Actinophrys sol was the only accessory species in all investigated sites. In general the soil at all sites was predominately by ciliates, meanwhile all flagellates species were absence in site 2.